PSAK 68 MEASUREMENT OF FAIR VALUE IFRS CONVERGENCE Fair Value Concept - Maulidah, Sindi; Noviyani, Lisma; Uzliawati, Lia (Review of Accounting and Taxation, 2024)
Abstract Purpose - This study aims to find out about the concept of fair value in PSAK 68: IFRS Convergence Fair Value Measurement, as a substitute for book value. The convergence of the application of new accounting standards is oriented towards the International Financial Reporting Standard (IFRS) issued by the International Accounting Standard Boards (IASB). In this new accounting standard, the concept of fair value is emphasized more than the concept of book value. This is what makes the difference and triggers this convergence to change the simpler book value model Design/methodology/approach - This study uses a descriptive qualitative method with a literature study approach on fair value measurement. Finding - The result of this study is the concept of fair value (fair value) that is currently considered to have an advantage over book value is a concept that is widely applied all over the world, as well as with accounting in Indonesia should be ready to apply the concepts of reasonable value in its accounting standards Originality – Paper Type – Research Paper